(untitled) (Diametros, 2017)
Leonard Nelson is known primarily as a critic of epistemology in the Neo-Kantian meaning of the term. The aim of this paper is to investigate the presuppositions and consequences of his critique. I claim that what has rarely been discussed in this context is the problem of the possibility of metaphysics. By the impossibility of epistemology Nelson means the possibility of metaphysical knowledge. I intend to devote this paper to the analysis of this problem in relation to the Neo-Kantian background.